2015
DOI: 10.15288/jsad.2015.76.474
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use to Facilitate a Suicide Attempt: An Event-Based Examination

Abstract: ABSTRACT. Objective: The current study is based on the hypothesis that alcohol-involved suicide attempts are characterized by lower premeditation and intent, but only when the use of alcohol is not motivated by the desire to facilitate the attempt. Test of this idea was conducted by comparing proximal suicide premeditation and intent of suicide attempts among three groups: individuals who (a) drank to facilitate the attempt (e.g., to "numb fears" about attempting), (b) drank for nonfacilitative motives, and (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…These associations calculated using the Chi-Square statistical test were not statistically significant ( p  > 0.05), though the overall direction of the findings were in keeping with studies from high-income countries [12, 15, 32]. It is possible that given a larger sample and more accurate measures of AUS, we would have found the differences we observed to be statistically significant.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These associations calculated using the Chi-Square statistical test were not statistically significant ( p  > 0.05), though the overall direction of the findings were in keeping with studies from high-income countries [12, 15, 32]. It is possible that given a larger sample and more accurate measures of AUS, we would have found the differences we observed to be statistically significant.…”
Section: Discussionsupporting
confidence: 66%
“…High levels of substance use during social events are associated with self-harm, independent of the level of suicidal intent, as a result of disinhibition, increased impulsivity, impaired judgement, increased feelings of depression or hopelessness, and the urge to escape a situation or to change the behaviour of someone else [13, 14]. In cases with higher levels of intent to die and premeditation, AUS may facilitate self-harm by easing the distress of engaging in self-harm [15]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that across the 24 hours prior to a suicide attempt, the AUA within a specific hour led to increased intensity of suicidal ideation in the subsequent hour, controlling for the prior hour level of suicidal ideation. Further, some individuals use alcohol prior to an attempt to facilitate the attempt (e.g., numb fears about attempting)(see (Bagge et al, 2015). This research demonstrates that a “one size fits all” model cannot be used to understand the role of AUA on suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol co‐ingestion may have a disinhibiting effect, with increased levels of impulsivity and/or self‐aggressive tendencies (Bagge & Sher, ). There is empirical evidence to suggest that a proportion of those who consume alcohol prior to their DSP episode have lower suicidal intent than those who do not, particularly those in which alcohol was consumed for nonfacilitative (i.e., for recreation) purposes as opposed to facilitative reasons (i.e., to numb fears or enhance toxicity of poisons; Bagge, Conner, Reed, Dawkins, & Murray, ).…”
mentioning
confidence: 99%